Malignant neck mass in disguise - atypical presentation of extraskeletal Ewing's sarcoma - Poh, Nuan Leng; Fijasri, Nurul Hafiez; Mohammad Azmi, Mohd Azem Fathi; Jasmani, Asraf Haslam; Wan Zain, Wan Zainira; Yunus, Dahziela; Zawawi, Norzaliana (Universiti Putra Malaysia, 2022)
Ewing’s sarcoma is the second most malignant bone tumour and commonly occurs in paediatric patients. Extraskeletal Ewing’s sarcoma can arise from the head and neck as the primary site of origin of the tumour despite being rare. This soft tissue tumour morphologically mimics Ewing’s sarcoma of bone. We report a case of extraskeletal Ewing’s sarcoma of the neck region in a 53-year-old lady who presented to the emergency department with a rapidly growing mass over three weeks associated with pain over the posterolateral neck region. It is challenging to reach the diagnosis at the first encounter as this lesion is found at an uncommon location and presented with a sebaceous cyst-like physical appearance.